2017
DOI: 10.1038/srep42488
|View full text |Cite
|
Sign up to set email alerts
|

In patients with chronic aplastic anemia, bone marrow–derived MSCs regulate the Treg/Th17 balance by influencing the Notch/RBP-J/FOXP3/RORγt pathway

Abstract: The standard treatment for aplastic anemia (AA) in young patients is a matched sibling hematopoietic stem cell transplant. Transfusion of a chronic AA patient with allogeneic bone marrow–derived mesenchymal stromal cells (BMMSCs) is currently being developed as a cell-based therapy, and the safety and efficacy of such transfusions are being continuously improved. Nevertheless, the mechanisms by which BMMSCs exert their therapeutic effects remain to be elucidated. In this study, mesenchymal stromal cells (MSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 31 publications
(43 reference statements)
1
37
0
Order By: Relevance
“…The tissue microenvironment into which MSCs migrate/are injected into also influences their immunosuppressive properties. MSCs located within an inflammatory microenvironment can suppress cytotoxic T cells ( 96 , 113 ), induce T regulatory cells ( 114 , 115 ), and stimulate macrophage polarization ( 116 ) (transition from an M1 to an M2 phenotype) thereby promoting an anti-inflammatory milieu. Furthermore, a recent study demonstrated that MSCs exert antibacterial effects ( 117 ) indicating that MSCs possess an immune function independent of the host's immune system.…”
Section: Mesenchymal Stem Cells As a Therapeutic Strategy For Frailtymentioning
confidence: 99%
“…The tissue microenvironment into which MSCs migrate/are injected into also influences their immunosuppressive properties. MSCs located within an inflammatory microenvironment can suppress cytotoxic T cells ( 96 , 113 ), induce T regulatory cells ( 114 , 115 ), and stimulate macrophage polarization ( 116 ) (transition from an M1 to an M2 phenotype) thereby promoting an anti-inflammatory milieu. Furthermore, a recent study demonstrated that MSCs exert antibacterial effects ( 117 ) indicating that MSCs possess an immune function independent of the host's immune system.…”
Section: Mesenchymal Stem Cells As a Therapeutic Strategy For Frailtymentioning
confidence: 99%
“…Previous studies indicate Tregs function in the progression of some kind of autoimmune diseases like SAA [13][14][15], To our knowledge, blood Tregs are significantly decreased in AA patients than their counterparts in normal people [16]. Furthermore, Tregs can also regulate the function of B cells and other non-T cells diametrically.…”
Section: Introductionmentioning
confidence: 70%
“…In addition, several previous studies have elucidated that treatment with CsA may increase the number of Tregs in patients with AA and other diseases ( 42 44 ). Previous studies have indicated good efficacy of CsA in the treatment of patients with AA, which may indicate that if it existed, the inhibition of Tregs by CsA may be limited and does not interfere with the treatment effect ( 1 , 45 47 ).…”
Section: Discussionmentioning
confidence: 99%